Recent Economic Developments and Prospects - Mottaghi, Lili (2015)
The global economy will grow 3 to 3.5 percent this year, 0.5 percent higher than last year s 2.6 percent, and surpassing the average growth rate of 3.1 percent during 2000-08, before the financial crisis. The magnitude of the gains will depend on, among other factors, the share of oil imports in gross domestic product (GDP). Oil exporters (including Russia) can see a sharp fall in growth deteriorating fiscal balances with significant regional consequences. Low oil prices have significantly affected the economies of the oil exporters - accounting for 2-3 of the countries in the region. Economic growth in Middle East and North Africa (MENA) is expected to continue on the same path in 2016. If the security situation in Libya improves and oil exports increase, the regional average can surge to 4 percent to 5 percent in 2016.